Cloeodes tovauna: a new species previously identified as Cloeodes aymore Massariol & Salles, 2011 (Ephemeroptera: Baetidae) - Amaral, I. F.; Cifuentes-Vargas, E. T.; Salles, F. F. (Zootaxa, 2025)
In this study, material previously attributed to Cloeodes aymore Massariol & Salles is recognized and described as a distinct new species. The description is based on nymphs and reared adults collected in the State of Minas Gerais, Southeastern Brazil. The key characteristics that differentiate this new species from its congeners in nymphal stage are: a) body color pattern dark brown on head, thorax and abdominal segments; b) inner margin of labial palp segment III with robust pectinate setae; c) terga with spines present on posterior margins of segments II–X. The adults can be distinguished by the following characteristics: a) thorax dark brown; b) abdominal segments I, VII–X brown; terga IV with median pair of brown spots; c) single intercalary vein between RA-RP1 (sometimes paired), ICu1-ICu2 and ICu2-CuP; d) hind wings present; e) forceps segment III oval; posterior margin of subgenital plate slightly convex at middle. The interactive key to the South American species of the genus was updated to include the new species.